(untitled) (Research, Society and Development, 2021)
The aim of this literature review was to evaluate the influence of the presence and absence of parents on child behavior during dental treatment, also seeking to analyze the point of view of parents and dentists on this topic, and how it can help professionals in providing guidance. correct regarding the inclusion of parents during their children’s consultations. The selection of studies used in this work was based on articles published in the last 10 years, published in PubMed/Medline, Scopus, LILACS, SciELO and Cocrhane. The results showed that there are numerous factors that influence the behavioral change of children, and the presence of parents during dental appointments is only beneficial in younger children, demonstrating that in other cases children do not show improvements in cooperation during dental treatment, regardless of whether the parents are present. Thus, it is possible to conclude that child behavior is not directly influenced by the presence or absence of parents, and it is necessary to evaluate other factors that are interconnected to the behavior of these children, analyzing case by case the advantages and disadvantages of the presence of parents during dental treatment.